Second-Harmonic Generation in Suspended AlGaAs Waveguides: A Comparative Study - Iännis Roland; Marco Ravaro; Stéphan Suffit; Pascal Filloux; Aristide Lemaître; Ivan Favero; Giuseppe Leo (Micromachines, 2020)
Due to adjustable modal birefringence, suspended AlGaAs optical waveguides with submicron transverse sections can support phase-matched frequency mixing in the whole material transparency range, even close to the material bandgap, by tuning the width-to-height ratio. Furthermore, their single-pass conversion efficiency is potentially huge, thanks to the extreme confinement of the interacting modes in the highly nonlinear and high-refractive-index core, with scattering losses lower than in selectively oxidized or quasi-phase-matched AlGaAs waveguides. Here we compare the performances of two types of suspended waveguides made of this material, designed for second-harmonic generation (SHG) in the telecom range: (a) a nanowire suspended in air by lateral tethers and (b) an ultrathin nanorib, made of a strip lying on a suspended membrane of the same material. Both devices have been fabricated from a 123 nm thick AlGaAs epitaxial layer and tested in terms of SHG efficiency, injection and propagation losses. Our results point out that the nanorib waveguide, which benefits from a far better mechanical robustness, performs comparably to the fully suspended nanowire and is well-suited for liquid sensing applications.